EFFECT OF HUMIC ACID AND SEAWEED EXTRACTS ON GROWTH AND YIELD OF POTATO PLANT (Solanum tubersum L) DESIREE CV. - Taha Z. Sarhan (Mesopotamia Journal of Agriculture)
This study was conducted in College of Agriculture Farms/University of Duhok. At the spring season 2009 on potato plants CV. Desiree. RCBD Design with two factors was applied to study the effect of Humic acid and two seaweed extracts Alga 600 and sea force 2 on potato plants. Humic acid and seaweed extracts treatments caused a significant increase in all vegetative growth and yield characteristics of potato CV desiree. The interaction between treatments also caused a significant effect and the plants which got a humic acid and sprayed with mixture of Alga 600 and sea force 2 gave the highest values of vegetative characters as compared with lowest values of control plants. Also the results appeared a positive significant effect of humic acid and seaweed extracts and their interactions on all yield quantitative characters